2017
DOI: 10.1080/16549716.2017.1366165
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the problem of obesity and associated cardiometabolic risk in black South African women – time for action!

Abstract: The PhD thesis of Gradidge, entitled ‘Factors associated with obesity and metabolic syndrome in an ageing cohort of black women living in Soweto, Johannesburg (Study of Women in and Entering Endocrine Transition [SWEET])’, attempts to understand the determinants of obesity and metabolic syndrome (MetS) in a population of urban-dwelling black South African women. A conceptual framework is presented, which positions obesity as the central risk factor for MetS, and includes the possible influence of socioeconomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Consistent with this, are ndings from previous studies which also reported the relationship of cardiometabolic risk with age, socioeconomic status, body composition and physical activity. [24,25] After controlling for confounders using logistic regression analysis, age and gender were the only variables that were still signi cantly associated with cardiometabolic risk using WHtR. This was such that older respondents and the female gender were more likely to have high cardio-metabolic risk compared to others.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this, are ndings from previous studies which also reported the relationship of cardiometabolic risk with age, socioeconomic status, body composition and physical activity. [24,25] After controlling for confounders using logistic regression analysis, age and gender were the only variables that were still signi cantly associated with cardiometabolic risk using WHtR. This was such that older respondents and the female gender were more likely to have high cardio-metabolic risk compared to others.…”
Section: Discussionmentioning
confidence: 96%
“… 29 , 30 Suggested interventions include encouraging participation in high-intensity activities, such as sports and aerobics, and discouraging sedentary behaviour. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status is a key determinant of obesity particularly among black African women [158] and also influences disease risk by promoting oxidative stress [155]. Accordingly, urinary concentrations of 8-iso-PGF2α were shown to increase with lower socioeconomic status in women [159].…”
Section: Environmental Socioeconomic and Lifestyle Factorsmentioning
confidence: 99%